Adherence to antiretroviral drug therapy in adult patients who are HIV-positive in Northwest Ethiopia: a study protocol. Issue 10 (31st October 2013) - Bezabhe, Woldesellassie M; Peterson, Gregory M; Bereznicki, Luke; Chalmers, Leanne; Gee, Peter
Abstract : Introduction: Achievement of optimal medication adherence and management of antiretroviral toxicity pose great challenges among Ethiopian patients with HIV/AIDS. There is currently a lack of long-term follow-up studies that identify the barriers to, and facilitators of, adherence to antiretroviral therapy (ART) in the Ethiopian setting. Therefore, we aim to investigate the level of adherence to ART and a wide range of potential influencing factors, including adverse drug reactions occurring with ART. Methods and analysis: We are conducting a 1-year prospective cohort study involving adult patients with HIV/AIDS starting on ART between December 2012 and March 2013. Data are being collected on patients' appointment dates in the ART clinics. Adherence to ART is being measured using pill count, medication possession ratio and patient's self-report. The primary outcome of the study will be the proportion of patients who are adherent to their ART regimen at 3, 6 and 12 months using pill count. Taking 95% or more of the dispensed ART regimen using pill count at given points of time will be considered the optimal level of adherence in this study. Data will be analysed using descriptive and inferential statistical procedures. Ethics and dissemination: Ethics approval was obtained from the Tasmania Health and Medical Human Research Ethics Committee and Bahir-Dar University's Ethics Committee. The results of the study will be reported in peer-reviewed scientific journals, conferences and seminar presentations.